The Copyright Wars - Peter Baldwin (Princeton University Press, 2014)
In 1948 several Soviet composers, including Dmitri Shostakovich, objected to the use of their music in an American spy film, The Iron Curtain, that was distinctly anti-Communist. These Soviet composers understandably feared the gulag for appearing in Hollywoodâ€™s first Cold War effort.1 Though their music was unchanged, they protested its political use. When Shostakovich sued in the United States, he failed. The works were in the public domain, thus freely available for anyoneâ€™s use, the composer had been credited, the film did not claim that he agreed with its views, and the music had not been distorted. How, the court asked, had the artistâ€™s rights been violated? â€œIs the standard to be good taste, artistic worth, political beliefs, moral concepts, or what is it to be?â€2 But in France a court ascertained â€œmoral damage.â€ The film was banned and the composers were awarded damages. In 1988 the director John Huston sued to prevent the Asphalt Jungle, which he had filmed in 1950 in black and white, from being shown on television in a colorized version. In the United States, according to the work-for- hire doctrine, the film studioâ€”and not the director it employsâ€”is the author. But in France, after Hustonâ€™s death that year, his children and his screenwriter invoked the continuing aesthetic claims, or â€œmoral rights,â€ that remain with authors in French law even after they have sold their works. Over the next six years, five different French courts first prevented screening, then allowed the film to be broadcast only if the directorâ€™s objections were publicized, and finally levied hefty fines on Turner Entertainment, the errant colorizers.